Letter about disturbances in China and secret societies (1900)
This 1900 diplomatic dispatch, issued by the Portuguese Consulate in Canton (Guangdong) on 12 June, forms part of the official Series A correspondence addressed to the Minister and Secretary of State for Foreign Affairs in Lisbon. Authored by Consul Joaquim Belchior Cabral Cruz, the document reports on the political and military situation in southern China amid the escalating Boxer Uprising in northern China. While asserting that calm nominally prevails in Canton, the author cautions that this stability is superficial, citing the presence of armed bands in Guangdong and Guangxi provinces and the ripple effects of unrest in Beijing since mid-May. The text references troop deployments by the Viceroy of Canton in response to rumours of uprisings in Guangxi, later attributed to local conflicts exploited by pirates. The dispatch also notes the appointment of Littung Han as interim Viceroy—a figure granted the high imperial honour of incorporating the Dragon motif into his robes—suggesting close ties to the imperial family. It further contextualises the anti-foreign activities of the Boxers in the north, their attacks on missionaries and converts, and anticipated foreign military intervention to restore order. Additionally, the consul briefly comments on trade along the Taur Shui River and the strategic implications of port access for Ilha Formosa (Taiwan), though declines to elaborate, acknowledging the matter falls under the jurisdiction of the colonial government there. This document provides critical insight into regional governance, imperial legitimacy, and foreign diplomatic perceptions during a period of intense upheaval in late Qing China.
Keywords: Anti-Foreign Activities; Armed Bands; Boxer Uprising; Calm Nominally Prevailing; Converts Persecution; Diplomatic Dispatch; Dragon Symbolism; Foreign Intervention; Guangdong Province; Guangxi province; Historical Record; Imperial Family Ties; Interim Viceroy; Joaquim Belchior Cabral Cruz; Littung Han; Missionaries Attacks; Northern China; Official Series A Correspondence; Political Military Situation; Portuguese Consulate in Canton; Portuguese Diplomatic Reports; Security Concerns; Southern China; Superficial Stability; Transcription; Viceroy of Canton